2004
DOI: 10.1177/0363546503259345
|View full text |Cite
|
Sign up to set email alerts
|

Articular Cartilage Lesions in 993 Consecutive Knee Arthroscopies

Abstract: Eleven percent of all knee arthroscopies show cartilage defects that may be suitable for cartilage repair procedures. However, the natural history of these lesions and the number of patients that will benefit from a cartilage repair procedure are so far unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
202
0
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 508 publications
(220 citation statements)
references
References 16 publications
(15 reference statements)
6
202
0
12
Order By: Relevance
“…The specific aims were to evaluate the feasibility of the program as determined by (1) adherence to the rehabilitation program, (2) clinical changes in knee function, (3) progression of the rehabilitation program, and (4) the occurrence of adverse events.…”
Section: T T Conclusionmentioning
confidence: 99%
“…The specific aims were to evaluate the feasibility of the program as determined by (1) adherence to the rehabilitation program, (2) clinical changes in knee function, (3) progression of the rehabilitation program, and (4) the occurrence of adverse events.…”
Section: T T Conclusionmentioning
confidence: 99%
“…However, several studies report cartilaginous lesions occurring preferentially in the medial compartment and/or in the medial femoral condyle. 1,12,28,31,[37][38][39][40] To recognize age-specific differences, patients were divided into two age subgroups: (A) subjects aged 18-50 years and (B) subjects aged 51-81 years. The majority of grade I lesions occurred in Group A (65%).…”
Section: Discussionmentioning
confidence: 99%
“…The accelerated group covered a significantly greater distance during the 6-minute walk test compared to the traditional group. Robertson et al 59 reported significant improvement over time (3,6,12, and 24 months) in distance covered during the walk test in 31 patients following ACI (age range, 19-60 years). Similar findings were recently reported by Ebert and colleagues 13 in 20 patients (age range, 15-65 years) following ACI and a 12-week rehabilitation program that focused on progressive weight bearing, progressive strengthening activities, and progressive neuromuscular control activities.…”
Section: Outcomes Related To Performancebased Measures Of Functionmentioning
confidence: 99%
“…7,31 In 2 large-scale studies of more than 25 000 knee arthroscopies, 60% of the operated knees demonstrated articular cartilage lesions. 11,74 Approximately 5% to 27% of patients younger than 45 years of age have articular cartilage lesions identified at arthroscopy, 3,11,31,74 and active individuals may be at even higher risk for articular cartilage injury than the general population. 22 In the short term, these lesions may lead to a loss of function and a significant decline in activity participation.…”
mentioning
confidence: 99%